Boosting of photocatalytic hydrogen evolution via chlorine doping of polymeric carbon nitride - Aleksandrzak, Malgorzata; Kijaczko, Michalina; Kukulka, Wojciech; Baranowska, Daria; Baca, Martyna; Zielinska, Beata; Mijowska, Ewa (Beilstein Journal of Nanotechnology, 2021)
Chlorine is found to be a suitable element for the modification of polymeric carbon nitride properties towards an efficient visible-light photocatalytic activity. In this study, chlorine-doped polymeric carbon nitride (Cl-PCN) has been examined as a photocatalyst in the hydrogen evolution reaction. The following aspects were found to enhance the photocatalytic efficiency of Cl-PCN: (i) unique location of Cl atoms at the interlayers of PCN instead of on its π-conjugated planes, (ii) slight bandgap narrowing, (iii) lower recombination rate of the electron–hole pairs, (iv) improved photogenerated charge transport and separation, and (v) higher reducing ability of the photogenerated electrons. The above factors affected the 4.4-fold enhancement of the photocatalytic efficiency in hydrogen evolution in comparison to the pristine catalyst.
Keywords: chlorine; doping; hydrogen evolution reaction; photocatalysis; polymeric carbon nitride